John Company at the Cape : a history of the agency under Pringle (1794-1815), based on a study of the "Cape of Good Hope factory records" - Arkin, Marcus (Department of Historical Studies, 2023)
For much of its long and influential career, the English East India Company (familiarly known as “John Company”) was not directly concerned with the Cape of Good Hope, and that Colony held no more than a very minor place on the fringes of its commercial affairs.